Effects of green silver nanoparticles on bacterial-infected in vitro Eucalyptus pellita F.Muell plant - Sawalha, Hanadi Akram Naser (2023)
Nanotechnology has emerged as a vibrant field of research in several modern scientific and engineering fields. The application and development of silver nanoparticles (AgNPs) have remarkably increased due to their distinctive features, including size (1-100 nm), shape, and antimicrobial properties. Diverse biomolecules and biological entities (prokaryotes and eukaryotes) are widely used as bio-stocks to create nanostructured materials. Green AgNPs provide non-toxic and sustainable materials to be used as antimicrobial agents. The growing demand for Eucalyptus species for industrial applications requires an efficient propagation strategy for rapidly and genetically producing improved trees. However, various microbial pathogens affecting the growth of Eucalyptus, which are considered the main concerns since they can cause long-term damage to Eucalyptus plantation. This study examined the effect of green AgNPs on the pathogen-infected in vitro Eucalyptus pellita (E. pellita) plants. Shoot regenerated in vitro from cotyledonary leaf explants of E. pellita were induced through direct organogenesis using (Murashige and Skoog) MS media supplemented with different concentrations (0.4, 1.3, 2.2, 3.1, 3.9 μM) of thidiazuron (TDZ), 6-benzylaminopurine (BAP) and kinetin (KIN). The elongated shoots were rooted in vitro using ½ MS media supplemented with different concentrations (0.5, 1, 1.5, 2, 2.5 μM) of indole-3-butyric acid (IBA) and 1-naphthaleneacetic acid (1-NAA), respectively.The highest shoot formation from cotyledonary leaves was observed in the MS media supplemented with 2.2 μM BAP, followed by 3.1 μM BAP, giving a mean of 7.4 and 6 shoots per explant, respectively. The highest root formation was observed in the ½ MS media supplemented with 1.5 μM IBA averaging 17.47 roots per explant. The regenerated plantlets were infected with three bacterial strains (Bacillus sp. EU_UPM1, Pntoea dispersa EU_UPM2 and Pntoea dispersa EU_UPM3). The results showed that the antibacterial effect of green AgNPs on infected plants was evaluated in vitro by the direct inoculation of 100 ppm of green AgNPs to the bacterial infected E. pellita plantlets. This research will create awareness of new aspirations to mass-produce the free pathogen-infected E. pellita plants.